Novel NMP split liver model recapitulates human IRI and demonstrates ferroptosis modulators as a new therapeutic strategy. (11th October 2021) - Nazzal, Mustafa; Madsen, Erik C.; Armstrong, Austin; van Nispen, Johan; Murali, Vidul; Song, Eric; Voigt, Marcus; Madnawat, Himani; Welu, Adam; Manithody, Chandrashekhara; Suri, Anandini; Krebs, Joseph; et al.
Abstract: Background: Almost 9%of deceased donor livers are discarded as marginal donor livers (MDL) due to concern of severe ischemia reperfusion injury (IRI). Emerging data supports ferroptosis (iron regulated hepatocellular death) as an IRI driver, however lack of robust preclinical model limits therapeutic testing. In this manuscript we describe the development of a novel rigorous internal control system utilizing normothermic perfusion of split livers to test ferroptosis regulators modulating IRI. Methods: Upon institutional approval, split human MDLs were placed on our normothermic perfusion machine, Perfusion Regulated Organ Therapeutics with Enhanced Controlled Testing (PROTECT), pumping arterial and portal blood. Experiment 1 compared right (UR) and left (UL) lobes to validate PROTECT. Experiment 2 assessed ferroptosis regulator Deferoxamine in Deferoxamine Agent Treated (DMAT) vs. No Agent Internal Control (NAIC) lobes. Liver serology, histology, and ferroptosis genes were assessed. Results: Successful MDL perfusion validated PROTECT with no ALT or AST difference between UR and UL (∆ALT UR: 235, ∆ALT UL: 212; ∆AST UR: 576, ∆AST UL: 389). Liver injury markers increased in NAIC vs. DMAT (∆ALT NAIC: 586, ∆ALT DMAT: ‐405; ∆AST NAIC: 617, ∆AST DMAT: ‐380). UR and UL had similar expression of ferroptosis regulators RPL8, HO‐1 and HIFα. Significantly decreased intrahepatic iron ( p  = .038), HO‐1 and HIFα in DMAT (HO‐1 NAIC: 6.93, HO‐1 DMAT: 2.74; HIFαNAIC: 8.67, HIFαDMAT: 2.60)and no hepatocellular necrosis or immunohistochemical staining (Ki67/Cytokeratin‐7) differences were noted. Conclusion: PROTECT demonstrates the therapeutic utility of a novel normothermic perfusion split liver system for drug discovery and rapid translatability of therapeutics, driving a paradigm change in organ recovery and transplant medicine. Our study using human livers, provides preliminary proof of concept for the novel role of ferroptosis regulators in driving IRI.